Can biological markers partially explain the link between the social environment and oral health? = ¿Pueden los marcadores biológicos explicar parcialmente la relación entre el entorno social y la salud oral? - Barboza Solís, Cristina 1986-
Understanding how the social world affects human's health by "getting under the skin" and penetrating the cells, organs and physiological systems of the body is a key tenet in public health research. Here, we propose the idea that socioeconomic position (SEP) can be biologically embodied, potentially leading to the production of health inequalities in oral health across population groups. Recent studies show that being exposed to chronic stress across the life course could impact our health. Allostatic load (AL) is a composite biological measure of overall physiological wear-and-tear that could allow a better understanding of the potential biological pathways playing a role in the construction of the social gradient in adult health. However, to use biological measures to better understand the mechanisms that construct health inequalities in oral health has not been tested systematically. The purposes of this New Perspective is to discuss the value of using composite biological markers, such as AL, to analyze oral health. This can allow a better understanding of the mechanisms leading to health inequalities in oral health, and add some valuable information for implementing health interventions.